Cost-effectiveness analysis of ultra-hypofractionated radiotherapy and conventionally fractionated radiotherapy for intermediate- to high-risk localized prostate cancer - He, Jiaoxue; Wang, Qingfeng; Hu, Qiancheng; Li, Changlin (Frontiers in Oncology, 2023)
Background Radiotherapy is an effective curative treatment option for intermediate- to high-risk localized prostate cancer. According to the HYPO-RT-PC trial (ISRCTN45905321), there was no significant difference in 5 years of follow-up in terms of failure-free survival, overall survival, urinary toxicity, and bowel toxicity, while erectile function decreased between ultra-hypofractionated radiotherapy with conventionally fractionated radiotherapy, except that the incidence of urinary toxicity in ultra-hypofractionated radiotherapy was higher at 1 year of follow-up. We evaluated the cost-effectiveness of ultra-hypofractionated radiotherapy and conventionally fractionated radiotherapy for intermediate- to high-risk localized prostate cancer from the Chinese payer’s perspective. Methods We developed a Markov model with a 15-year time horizon to compare the cost and effectiveness of ultra-hypofractionated radiotherapy with those of conventionally fractionated radiotherapy for localized intermediate- to high-risk prostate cancer. The outcomes were measured in quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), and willingness-to-pay (WTP). Univariable and probability sensitivity analyses were performed to evaluate the robustness of the Markov model. Results Based on the Markov model, conventionally fractionated radiotherapy yielded 2.32 QALYs compared with 2.14 QALYs in ultra-hypofractionated radiotherapy in China. The cost of ultra-hypofractionated radiotherapy was found to be decreased by about 14% folds ($4,251.04) in comparison with that of conventionally fractionated radiotherapy. The ICER of conventionally fractionated radiotherapy versus that of ultra-hypofractionated radiotherapy was $23,616.89 per QALY in China. The failure-free survival with grade 2 or worse urinary toxicity and the discount rate per annum were the most sensitive parameters utilized in ultra-hypofractionated radiotherapy. The cost-effectiveness acceptability curve showed that conventionally fractionated radiotherapy had 57.7% probability of being cost-effective under the Chinese WTP threshold. Conclusion From the perspective of Chinese payers, ultra-hypofractionated radiotherapy was not a cost-effective strategy compared with conventionally fractionated radiotherapy for patients with localized intermediate- to high-risk prostate cancer. Nevertheless, reduction of the grade 2 or worse urinary toxicity of ultra-hypofractionated radiotherapy could alter the results.